Analysis of Technical Training Needs for the Pioneer Battalion of Brimob Polda Metro Jaya in The Context of Securing The National Capital - Tabrani Koto; Basir Basir; Riska Sri Handayani (International Journal of Social Service and Research, 2023)
This research analyzes the technical training needs required by the Mobile Brigade Pioneer Battalion of Polda Metro Jaya in securing the National Capital City. Securing the National Capital is a complex challenge and requires high readiness and competence from the police, especially the Pioneer Battalion. In this research, the author uses a qualitative approach with the Training Need Analysis (TNA) analysis method, which involves questionnaires and a literature study. The results of the analysis show that the Pioneer Battalion is widely applied in various security tasks, which include handling high-intensity crime threats and managing natural disasters. The involvement of the Vanguard Battalion generally plays a role in supporting regional police when the intensity of the threat reaches a high escalation. Training uses a training manual published by the Foster Police Department. The research results show that there is still potential to improve training. In this analysis, the author emphasizes training based on actual needs for securing the National Capital, enhancing services to the community, and preparing to face future threats. In conclusion, this research identifies the importance of technical training in securing the National Capital by the Mobile Brigade Pioneer Battalion of Polda Metro Jaya. Based on the analysis, it is recommended to provide training that is not only related to the tasks and duties of the Pioneer Battalion in the context of securing the capital. Because the involvement of the pioneer battalion was extensive and not only related to security. The development and improvement of technical training that is relevant to the actual needs for security of the National Capital will strengthen the readiness and competence of Pioneer Battalion members in carrying out complex security tasks involving various other security aspects.